Notes on Financial System Development and Political Intervention - Song. Fenghua; Thakor, Anjan (World Bank, Washington, DC, 2013)
The paper studies the impact of political intervention on a financial system that consists of banks and financial markets and develops over time. In this financial system, banks and markets exhibit three forms of interaction: they compete, they complement each other, and they co-evolve. Coevolution is generated by two new ingredients of financial system architecture relative to the existing theories: securitization and risk-sensitive bank capital. The authors show that securitization propagates banking advances to the financial market, permitting market evolution to be driven by bank evolution, and market advances are transmitted to banks through bank capital. Then they examine how politicians determine the nature of political intervention designed to expand credit availability. The authors find that political intervention in banking exhibits a U-shaped pattern, where it is most notable in the early stage of financial system development (through bank capital subsidy in exchange for state ownership of banks) and in the advanced stage (through direct lending regulation). Despite expanding credit access, political intervention results in an increase in financial system risk and does not contribute to financial system evolution. Numerous policy implications are drawn out.